Representation of Aloneness in Forever Alone Guy Comic Strips - Pricillia Chandra; Ribut Basuki (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2017)
This study aims to discuss the representation of aloneness in Forever Alone Guy comic strips. The purpose of this research is to find out how the meaning of aloneness is constructed in the representation of Forever Alone Guy through the theory of representation described by Stuart Hall (1997, 2013). In the theory suggested by Hall, it is described that there are two ways to be done in creating representation. Those ways are through language/sign and mental representation. The mental representation is the only way used in this research with a reason that this analysis focuses to the stigmas attached to the concept of aloneness. The analysis shows that the construction of meaning is done through embedding clusters of negative stigmas to the three entities: single, alone and lonely. Thus, through the analysis, it can be concluded that the dominant meaning which represents being single and alone as the ‘imperfect’ condition plays an important role in the construction of the meaning